Rozmiary i zróżnicowanie populacji więziennej w Polsce w okresie obowiązywania ustawodawstwa karno-wykonawczego z 1997 roku - Nawój-Śleszyński, Aldona (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The size of the prison population, its size and dynamics understood as the develop-mental tendency of this phenomenon over a specific period of time as well as its structure, has a high cognitive value related to the punitive nature of the criminal justice system. It also serves to assess the values of the penitentiary system, and in particular to implement in practice the guiding principle of the execution of the penalty of deprivation of liberty, which is the principle of individualization. The study presents extensive statistical data on this problem from 1997 to the present.
Keywords: więzienie; przeludnienie jednostek penitencjarnych; skazani